Maintaining Language Standards in Newspaper Discourse (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses newspaper discourse and maintaining language norms in it. It examines the factors that led to the emergence of research on newspaper gender discourse and provides the necessary foundations and examples.